Intelligent emotion - Wilks, Frances (Arrow, 1998)
One of the projects facing both the individual and society as a whole is the development of emotional literacy. Just as human beings learn to read, so we can become literate about our emotions. The choice between learning to understand and transform our emotions or allowing them to run - and in some cases - ruin our lives.